Lost and found: different integration patterns of the Sudanese Lost Boys living in Kansas City area after resettlement - Mabeya, Danvas Ogeto (Kansas State University, 2011)
The United States has resettled unaccompanied minors before. In the 1960s and 1970s, minors from Indochina were resettled in the United States. In the 1970s, the U.S accepted 14,000 unaccompanied minors from Cuba through Operation Peter Pan. Many of these Cuban minors, aged five to eighteen, were sent to the United States by parents fearing their children would be indoctrinated in communist schools. In the case of these minors, they arrived in the United States with the consent of their still-living family members. In contrast, about 3,500 Sudanese Lost Boys were resettled in the United States in 2000, and more recently in 2010, 53 “lost children” from Haiti were brought to the United States following a devastating earthquake. This study investigated the integration and assimilation patterns of the Sudanese Lost Boys in the Kansas City area with the purpose of understanding the sociological impact on these Boys from their own perspective. As opposed to previous studies done on these Boys in Kansas and other areas in the United States, the present study used interview-based research and analyzed data using both qualitative and quantitative research methodologies. The study concluded that the Lost Boys were both “Lost” and “Found” in complex ways. The study found that unaccompanied refugees labeled as minors at the time of resettlement integrated more “successfully” than those resettled as adults. Minor Boys received certain advantages over Boys who were labeled legal adults. Over time, those resettled as minors accumulated more social capital relevant in American society, while those resettled as legal adults fell behind. The findings highlighted problems associated with age-based treatment of refugees, especially in the case of the Boys who were arbitrarily classified as adults. Assigned ages significantly impacted their assimilation process into American society. Unlike those Boys resettled as minors, legal adults did not have access to structure and immersion opportunities afforded by foster families, formal education, and social activities. This study concluded that age-based disadvantage was evident in the case of the Lost Boys.
Keywords: Refugees; Minors; Sudan; Legal adults; Social capital; Assimilation; African Studies (0293); Sociology (0626)